Pengaruh Struktur Kepemilikan dan Karakteristik Dewan Direksi terhadap Kebijakan Pembayaran Dividen Perusahaan Manufaktur di Indonesia - Muhammad Raditya Adhimukti; Henny Setyo Lestari (Universitas Batanghari, 2022)
The purpose of this research is to conclude the impact of ownership structure and board characteristics on dividend payout ratio and dividend yield. The sample in this study are companies from the manufacturing sector listed on Indonesia Stock Exchange in 2017-2021. The sampling technique used in this study is purposive sampling and the analysis method is tobit model. The independent variables in this study are institutional ownership, concentrated ownership, board size, female board member, and independent board member, and the control variable are firm age, financial leverage, firm size, and return on assets, with the dividend payout ratio and dividend yield as the dependent variable. The results show that independent board member and firm size have a positive effect on dividend payout ratio and dividend yield, while institutional ownership, concentrated ownership, board size,and financial leverage, have no effect on dividend payout ratio and dividend yield. On the other hand, female board member have a positive effect on dividend yield but no effect on dividend payout ratio, and return on assets show a positive effect on dividend payout ratio but no effect on dividend yield. This study is expected to give implication for company managers and investor. By paying attention to the indicators that lead the company to make a good dividend policy, and also to be a source of information for investors to see the dividend payout ratio and dividend yield given by the company to shareholders.